Dynamics of Pyridine Adsorption on Gold(111) Terraces in Acid Solution from in-Situ Scanning Tunneling Microscopy under Potentiostatic Control - Andreasen, Gustavo (1997)
The adsorption of pyridine (Py) on Au(111) terraces produced from aqueous 0.1 M HClO4 + 10-3 M Py at 298 K was studied in the potential range 0.15 V < E < 0.55 V (vs SHE) by in-situ scanning tunneling microscopy. When E ≥ Epzc, the potential of zero charge of the substrate, both ordered and disordered domains can be observed. Ordered domains correspond to vertically adsorbed Py molecules forming a (4 × 4) hexagonal lattice with the nearest neighbor distance d = 0.38 nm, and corrugation z = 0.04 nm. The ordered adsorbate structure disappears for E < Epzc, but it is recovered several minutes after stepping E backward to E > Epzc, as expected for a reversible potential-step-induced surface process. The surface concentration of adsorbed Py molecules resulting from the (4 × 4) lattice is close to 1 × 10-9 mol/cm2, a figure exceeding the average integral surface concentration value obtained from electroadsorption measurements. Therefore, disordered domains would be related to a mobile diluted Py adsorbate coexisting with ordered Py adsorbate domains leading to a nonhomogeneous Py adsorbate layer at the positively charged Au(111) terraces.